Choice of medical tactics and preliminary results of surgical treatment of the closed injuries of a brachial plexus combined with craniocerebral trauma - Dubyna, G. I. (Ukrainian Neurosurgical Journal, 2005)
In clinic of regenerative neurosurgery from 1993 to 2003 inspection of 348 patients with the closed injuries of a brachial plexus (BP) was held, 90 (25,8 %) from which have received BP trauma, combined with craniocerebral trauma. Damages, combined with craniocerebral trauma not only burdened the general current of trauma, but also being in close interaction results in increase of complications and death rate. In due time put diagnosis of the closed injuries of a brachial plexus received in a combination with craniocerebral trauma, and duly choice adequate neurosurgery treatments was the basic task during treatment. Clinical symptoms features of closed injuries of a brachial plexus were studied. The algorhythm of diagnostic and medical actions realization at victims with injuries of a brachial plexus was elaborated.